Angiogenesis and wound repair: when enough is enough - DiPietro, Luisa A. (Journal of leukocyte biology, 2016)
Review on novel concepts in wound angiogenesis; although more capillaries are generally considered better, new studies suggest otherwise. All animals heal, and the ability to heal is requisite for human health. One aspect of repair that has always been considered to be essential for adequate healing is the creation of a new vasculature via angiogenesis. As adult skin wounds heal, a period of rapid and robust capillary growth creates a vascular bed that has many fold more capillaries than does normal tissue. Over time, most of the newly formed capillaries regress, resulting in a final vascular density similar to that of normal skin. Certainly, new capillaries are necessary to bring nutrients, immune cells, and oxygen to healing wounds. Yet, the presumed functional importance of an overabundance of capillaries has recently been challenged, creating questions about whether excess capillary growth is truly necessary for healing. In particular, studies of wounds that heal exceptionally quickly and with less scar formation, such as those in fetal skin and oral mucosa, show that these tissues heal with a reduced angiogenic burst composed of more mature vessels that provide better oxygenation. The level of angiogenesis in wounds often correlates with the inflammatory response, largely because inflammatory cells produce an abundance of proangiogenic mediators. Both the selective reduction of inflammation and the selective reduction of angiogenesis have now been suggested as ways to improve scarring. These concepts link excessive inflammation and the production of a dense but poorly perfused capillary bed to inferior healing outcomes.